Early Discontinuation and Related Treatment Costs After Initiation of Basal Insulin in Type 2 Diabetes Patients: A German Primary Care Database Analysis - Anderten, Helmut (J Diabetes Sci Technol, 2015)
Aims: The aim was to compare early discontinuation and related treatment costs in type 2 diabetes in primary care after initiation of insulin glargine or human basal insulin (NPH). Methods: Overall, 2765 glargine and 1554 NPH patients from 1072 general practices were analyzed (Disease Analyser). Early discontinuation was defined as switching to a different basal insulin or another insulin treatment regimen within 90 days after first basal insulin prescription (index date, ID). Treatment costs were assessed 365 days prior and post ID in both groups. Propensity score matching and linear regression was used to adjust cost differences (post vs prior ID: discontinued vs continued patients) for age, sex, diabetes duration, antidiabetic comedication, diabetologist care, disease management program participation, costs before ID, and Charlson Comorbidity Index. Results: Within 3 months after ID, 13% of glargine patients switched to other insulin treatment regimens (NPH: 18%; P < .05). After propensity score matching, adjusted cost differences in 146 discontinued versus 1342 continued glargine patients were calculated (NPH: 146 vs 1342). Diabetes-related prescription costs were lower among persistent glargine patients compared to persistent NPH patients (EUR–49 [19]; P = .0109). Mean cost difference for diabetes-related prescriptions was lower among those who persisted on glargine compared to those who switched to other treatment regimens (EUR–74 [42], P = .0780). Conclusions: Treatment persistence within 3 months after basal insulin initiation was significantly higher under insulin glargine compared to NPH. Diabetes-related prescription costs were significantly lower among patients who adhered to insulin glargine compared to persistent NPH patients.